Aflatoxins as a risk factor for liver cirrhosis: a systematic review and meta-analysis - Abraham Nigussie Mekuria; Michael N. Routledge; Yun Yun Gong; Mekonnen Sisay (BMC, 2020)
Abstract Background Liver cirrhosis is characterized by fibrosis and nodule formation in the liver, due to a chronic injury, and subsequent alteration of the normal architecture of the liver. Even though there is a huge effort to elucidate the possible etiologic factors of liver cirrhosis, a significant number of cases are cryptogenic, especially in Sub Saharan Africa, where there is a high burden of aflatoxin exposure. Aflatoxins are known to cause hepatocellular carcinoma, which share similar etiologic factors with liver cirrhosis. This study aimed to assess the association between aflatoxin exposure and the risk of liver cirrhosis. Methods Relevant studies were identified through systematic searches conducted in Ovid MEDLINE, PubMed and Google Scholar. Also, by searching the references of retrieved articles. The abstracts and full text were screened for eligibility and the risk of bias was assessed for each study using Joanna Briggs Institute (JBI) critical appraisal checklist for observational studies. The extracted data from included studies using Microsoft Excel were exported to Stata software version 15.0 for analyses. The overall pooled estimation of outcomes was calculated using a random-effects model of DerSimonian-Laird method at a 95% confidence level. The heterogeneity of studies was determined using I2 statistics. The presence of publication bias between studies was evaluated using the Begg's and Egger's tests and funnel plot. The protocol of this systematic review and meta-analysis was registered in the Prospero database with reference number ID: CRD42019148481. Results A total of 5 studies published between the years 2005 and 2018 that met the pre-defined inclusion and exclusion criteria were included. The meta-analysis showed that a significant increase in the risk of liver cirrhosis is associated with aflatoxin exposure (unadjusted pooled odds ratio (OR) = 3.35, 95% CI: 2.74-4.10, p = 0.000; I2 = 88.3%, p = 0.000; adjusted OR = 2.5, 95% CI: 1.84-3.39, p = 0.000; I2 = 0%, p = 0.429). Conclusions The present meta-analysis suggests that aflatoxin exposure is associated with a higher risk of liver cirrhosis.